Mutations in rpoA affect expression of anaerobically regulated genes in Salmonella typhimurium. - Lombardo, M J (1991)
oxrB8, a mutation that diminishes the anaerobic induction of pepT and other anaerobically regulated, oxrA (fnr)-dependent Salmonella typhimurium genes, is an allele of rpoA, the gene for the alpha subunit of RNA polymerase. Four additional rpoA mutations that affect anaerobic pepT expression have been isolated after localized mutagenesis of the rpoA region. All but one of these rpoA mutations appear to have relatively specific effects on genes that require the OxrA (FNR) protein, a positive transcriptional regulator of a family of anaerobically expressed genes. All of these mutations lead to amino acid substitutions in the C-terminal region of the alpha subunit. These results taken with a number of previous observations suggest a role for the alpha subunit in the interaction between RNA polymerase and positive transcriptional regulatory proteins. They also suggest that the C-terminal region of alpha is important for these interactions.